"People first": Factors that promote or inhibit community transformation. Issue 3 (27th May 2019) - Brown, Mary Ellen; Baker, Birgitta L.
ABSTRACT: Residents are key assets in community change. Despite this, little is known about residents' perspectives regarding factors that facilitate or inhibit successful planning for neighborhood transformation. We conducted focus groups with residents of a low-wealth community involved with a neighborhood planning initiative and examined a planning document to elicit lived experience perspectives. Using Colaizzi's approach to phenomenology, the following themes emerged: (1) trust; (2) resident-driven transformation; (3) sense of community and cohesion; (4) engagement and collective action; and (5) openness to transformation. Attending to the factors identified by neighborhood residents can inform community development planning and practice.